2016
DOI: 10.1080/15569543.2016.1199572
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemistry, toxicity and feeding inhibitory activity ofMelissa officinalisL. essential oil against a cosmopolitan insect pest;Tribolium castaneumHerbst

Abstract: Tribolium castaneum considered as an economically worldwide insect pest for agricultural and medicinal aspects. Synthetic chemicals have been used in the management of T. castaneum but their residual problems have been renovated the interest in ecofriendly safe materials such as plant essential oils. In the present study, toxicity and antifeedant effects of an essential oil from Melissa officinalis as well-known medicinal plant investigated against T. castaneum. Chemical analysis indicated g-terpinene, carvacr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…The adults of R. dominica were also susceptible to the fumigation of essential oils extracted from Eucalyptus globulus Labill (24-h LC 50 = 3.529 μL/L), Lavandula stoechas L. (24-h LC 50 = 5.660 μL/L), and Apium graveolens L. (24-h LC 50 = 53.506 μL/L) [ 37 , 38 ]. The fumigation of the essential oils of Lippia citriodora Kunth (24-h LC 50 = 37.349 μL/L), Melissa officinalis L. (24-h LC 50 = 19.418 μL/L), and Teucrium polium L. (24-h LC 50 = 20.749 μL/L) resulted in significant mortality in T. castaneum [ 39 , 40 , 41 ]. The essential oils of Schinus molle L. (48-h LC 50 = 806.50 μL/L) and Artemisia sieberi Besser (24-h LC 50 = 33.80 μL/L) also had notable fumigant toxicity against the adults of T. granarium [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The adults of R. dominica were also susceptible to the fumigation of essential oils extracted from Eucalyptus globulus Labill (24-h LC 50 = 3.529 μL/L), Lavandula stoechas L. (24-h LC 50 = 5.660 μL/L), and Apium graveolens L. (24-h LC 50 = 53.506 μL/L) [ 37 , 38 ]. The fumigation of the essential oils of Lippia citriodora Kunth (24-h LC 50 = 37.349 μL/L), Melissa officinalis L. (24-h LC 50 = 19.418 μL/L), and Teucrium polium L. (24-h LC 50 = 20.749 μL/L) resulted in significant mortality in T. castaneum [ 39 , 40 , 41 ]. The essential oils of Schinus molle L. (48-h LC 50 = 806.50 μL/L) and Artemisia sieberi Besser (24-h LC 50 = 33.80 μL/L) also had notable fumigant toxicity against the adults of T. granarium [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The fumigant toxicity of some plant-derived essential oils against O. surinamensis, R. dominica, T. castaneum and T. granarium has been documented in previous studies; it was found that the essential oils of Agastache foeniculum (Pursh) Kuntze, Achillea filipendulina Lam., and Achillea millefolium L. with respective 24-h LC 50 values of 18.781, 12.121, and 17.977 µL/L, had high toxicity on the adults of O. surinamensis [31,[34][35][36]. The adults of R. dominica were also susceptible to the fumigation of essential oils extracted from Eucalyptus globulus Labill (24-h LC 50 [39][40][41]. The essential oils of Schinus molle L. (48-h LC 50 = 806.50 µL/L) and Artemisia sieberi Besser (24-h LC 50 = 33.80 µL/L) also had notable fumigant toxicity against the adults of T. granarium [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…officinalis has been extensively cultivated for its characteristic lemon-scented oil [25,26]. M. officinalis leaves contain 0.05-0.15% EO in fresh material and 0.1-0.45% EO in dried material, respectively [27]. Due to its digestive and antispasmodic properties, the leaves of M. officinalis are utilized in traditional medicine to treat moderate abdominal disorders and biliary dyskinesia [28].…”
Section: Introductionmentioning
confidence: 99%
“…It was primarily affected by leaf hair traits, not by female fecundity (host quality). Moreover, plant trichomes produce large amounts of essential oil, substances from the group of secondary metabolites play the role of a defensive mechanism of a plant against the attack of various pathogens or herbivorous [67,[73][74][75]. Presumably, in the present study, the composition of essential oils produced by the tested medicinal plants also influenced the acceptance and plant colonization by spider mites as well as their biological parameters.…”
Section: Discussionmentioning
confidence: 59%
“…According to Won-Il et al [80], sage oil applied to T. urticae caused more than 80% of adult mortality. However, M. officinalis antifeedant effect was also demonstrated against Tribolium castaneum [74], while O. basilicum showed a contact and fumigant toxicity against stored-food mite Tyrophagus putrescentiae [81].…”
Section: Discussionmentioning
confidence: 99%